Bladder underactivity after prolonged stimulation of somatic afferent axons in the tibial nerve in cats. Issue 7 (10th April 2018) - Li, Shun; Theisen, Katherine; Browning, Jeffery; Shen, Bing; Wang, Jicheng; Roppolo, James R.; de Groat, William C.; Tai, Changfeng
Abstract : Aims: To establish an animal model of bladder underactivity induced by prolonged and intense stimulation of somatic afferent axons in the tibial nerve. Methods: In seven cats under α‐chloralose anesthesia, tibial nerve stimulation (TNS) of 30‐min duration was repeatedly (3‐8 times) applied at 4‐6 times threshold (T) intensity for inducing a toe twitch to produce bladder underactivity determined by cystometry. Naloxone (1 mg/kg, i.v.) was administered to examine the role of opioid receptors in TNS‐induced bladder underactivity. Results: After prolonged (1.5‐4 h) and intense (4‐6T) TNS, a complete suppression of the micturition reflex occurred in six cats and an increase in bladder capacity to about 150% of control and a decrease in the micturition contraction amplitude to 50% of control occurred in one cat. The bladder underactivity was maintained for at least 1‐1.5 h. Naloxone reversed the bladder underactivity, but an additional 30‐min TNS removed the naloxone effect. Conclusions: The results indicate that prolonged and intense activation of somatic afferent axons in the tibial nerve can suppress the central reflex mechanisms controlling micturition. This animal model may be useful for examining the pathophysiology of neurogenic bladder underactivity and for development of new treatments for underactive bladder symptoms.